The Role of Social Capital in the Management of Payakabung Village Enterprises in South Sumatera Province - Annada Nasyaya (Jurnal Studi Sosial dan Politik, 2021)
Payakabung Village as the best village related to village financial management has good institutional social capital. Hence, it makes the village community builds Village-Owned Enterprises (BUMDes) to increase the socio-economic through local potential. However, even though Payakabung Village has many achievements and potentials, the community still has not good knowledge in managing this potential so that the role of social capital is needed to increase the Payakabung BUMDes, create an impact on the social community and economic activities. The method of this study used a qualitative descriptive based on the community of Payakabung Village and its BUMDes. The primary data sources were obtained from direct interviews, field observations, and literature studies. Meanwhile, the validity of the data obtained by the triangulation technique through comparing the data. The results of this study showed, the Payakabung BUMDes already had superior distinctive products developed, for example, citronella oil, oyster mushrooms, and toman fish ponds. In its management, social capital played an important role in Payakabung BUMDes' success. On the other hand, social capital had an impact on economic and social activities at the Payakabung BUMDes. The social capital element in BUMDes is providing capital assistance to increase the communitys' socio-economy, collaborating with partnerships to maximize local potential and improve transparent and accountable good village governance. We give the suggestions for BUMDes to improve their partnership cooperation so that the assistance provided is not only limited to providing funds but also giving requires mentoring and entrepreneurship training for local businesses.